2007
DOI: 10.1002/adma.200602149
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Piezo‐ and Pyroelectric Phases of BaZrO3 and SrTiO3

Abstract: Pyro‐ and piezoelectric quasiamorphous thin films of BaZrO3 and SrTiO3 are reported. This is the first instance of a polar amorphous solid being created from a compound that does not from polar crystalline polymorphs. The pyroelectric and the piezoelectric properties of the quasi‐amorphous SrTiO3 are of the same order of magnitude (10–50 %) as those of the most commonly used crystalline pyro‐ and piezo‐electric materials, such as BaTiO3, Pb(Ti,Zr)O3, and LiNbO3 (see figure).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 16 publications
1
47
0
Order By: Relevance
“…As in our earlier work on MAPbBr 3 (22), we used periodic pulse pyroelectric measurements (45)(46)(47) to determine whether tetragonal MAPbI 3 is polar along its c axis. Pyroelectric currents can be distinguished from other possible thermally stimulated electric response (TSER) (thermoelectricity or flexoelectricity) (22,48) by heating once one, and once the other side of the crystal periodically.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in our earlier work on MAPbBr 3 (22), we used periodic pulse pyroelectric measurements (45)(46)(47) to determine whether tetragonal MAPbI 3 is polar along its c axis. Pyroelectric currents can be distinguished from other possible thermally stimulated electric response (TSER) (thermoelectricity or flexoelectricity) (22,48) by heating once one, and once the other side of the crystal periodically.…”
Section: Resultsmentioning
confidence: 99%
“…A periodic temperature change (Chynoweth) method, was used to measure pyroelectricity (45)(46)(47). A general scheme of the setup (heat generation and pyroelectric current measurement) is visualized in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Lubomirsky and coworkers [75,[94][95][96] presented experimental data on perovskite thin films, which strongly suggest that a strain gradient can pole an amorphous material when it is thermally treated in a special way. It was shown that during such treatment the material is passing between two different amorphous states.…”
Section: Plastic Flexoelectricitymentioning
confidence: 99%
“…The anisotropy of the refractive index and the development of in-plane compressive stress may serve as unambiguous indicators of the transformation into the quasi-amorphous phase. In contrast to the refractive index, which decreases during the transformation of the amorphous into the quasi-amorphous phase, the dielectric constant increases during this transformation by 15-40% but remains far smaller than the dielectric constant of the corresponding crystalline phases ($22 and $33 for quasi-amorphous SrTiO 3 and BaTiO 3 , respectively [5,10] ). Monitoring changes in refractive indices, in-plane stress, and dielectric constant can be an efficient tool for tailoring film preparation conditions.…”
Section: Preparation and Physical Properties Of Quasi-amorphous Thin mentioning
confidence: 86%
“…[5] Subsequent investigation of this phase, called quasi-amorphous, [6][7][8][9] confirmed the conclusion that compounds that do not form polar crystalline polymorphs may nevertheless form polar quasi-amorphous phases that exhibit pyro-and piezoelectricity. [10] This hypothesis was later confirmed by the observation of the quasi-amorphous phase in SrTiO 3 and BaZrO 3 films. Data from extended X-ray absorption fine structure spectroscopy (EXAFS) and X-ray photoelectron spectroscopy (XPS) led to the development of a theory that describes the formation and microscopic origin of polarity in quasi-amorphous films.…”
Section: Introductionmentioning
confidence: 85%